The Impact of Web-Based Feedback on Physical Activity and Cardiovascular Health of Nurses Working in a Cardiovascular Setting: A Randomized Trial - Reed, Jennifer L.; Cole, Christie A.; Ziss, Madeleine C.; Tulloch, Heather E.; Brunet, Jennifer; Sherrard, Heather; Reid, Robert D.; Pipe, Andrew L. (Frontiers in Physiology, 2018)
A disconcerting proportion of Canadian nurses are physically inactive and report poor cardiovascular health. Web-based interventions incorporating feedback and group features may represent opportune, convenient, and cost-effective methods for encouraging physical activity (PA) in order to improve the levels of PA and cardiovascular health of nurses. The purpose of this parallel-group randomized trial was to examine the impact of an intervention providing participants with feedback from an activity monitor coupled with a web-based individual, friend or team PA challenge, on the PA and cardiovascular health of nurses working in a cardiovascular setting. Methods: Nurses were randomly assigned in a 1:1:1 ratio to one of the following intervention “challenge” groups: (1) individual, (2) friend or (3) team. Nurses wore a Tractivity® activity monitor throughout a baseline week and 6-week intervention. Height, body mass, body fat percentage, waist circumference, resting blood pressure (BP) and heart rate were assessed, and body mass index (BMI) was calculated, during baseline and within 1 week post-intervention. Data were analyzed using descriptive statistics and general linear model procedures for repeated measures. Results: 76 nurses (97% female; age: 46 ± 11 years) participated. Weekly moderate-to-vigorous intensity PA (MVPA) changed over time (F = 4.022, df = 4.827, p = 0.002, η2 = 0.055), and was greater during intervention week 2 when compared to intervention week 6 (p = 0.011). Daily steps changed over time (F = 7.668, df = 3.910, p < 0.001, η2 = 0.100), and were greater during baseline and intervention weeks 1, 2, 3, and 5 when compared to intervention week 6 (p < 0.05). No differences in weekly MVPA or daily steps were observed between groups (p > 0.05). No changes in body mass, BMI or waist circumference were observed within or between groups (p > 0.05). Decreases in body fat percentage (−0.8 ± 4.8%, p = 0.015) and resting systolic BP (−2.6 ± 8.8 mmHg, p = 0.019) were observed within groups, but not between groups (p > 0.05). Conclusions: A web-based intervention providing feedback and a PA challenge initially impacted the PA, body fat percentage and resting systolic BP of nurses working in a cardiovascular setting, though increases in PA were short-lived. The nature of the PA challenge did not differentially impact outcomes. Alternative innovative strategies to improve and sustain nurses' PA should be developed and their effectiveness evaluated.